The household, the street and the labour market: masculinities and homosocial solidarity networks of Afghan migrant boys in a squatter neighbourhood in Istanbul. Issue 2 (3rd April 2019) - Bozok, Mehmet; Bozok, Nihan
ABSTRACT: This study focuses on how undocumented Afghan migrant boys construct homosocial solidarity networks in the absence of their families in a squatter neighbourhood in Istanbul, Turkey. Based on the findings of qualitative field research conducted in 2015, this study argues that the homosocial solidarity networks among young Afghan migrant boys are developed in three different spatial contexts: the household, the street and the labour market . These homosocial solidarity networks enable them to survive in a foreign country which is full of challenges. Being a part of those networks provides employment in a competitive labour market, as well as security. In that process, while trying to survive, young Afghan migrant boys engage in gender stretching in the household. At the same time, in spite of their fragility as undocumented young migrants in a foreign land, they develop stern-yet-fragile transnational migrant masculinities challenging local masculinities in the public sphere, at the cost of losing their childhood in an early age.